PEMBELAJARAN MEMAHAMI JENIS - JENIS PEKERJAAN PADA SISWA SEKOLAH DASAR KELAS IV DENGAN MENGGUNAKAN MODEL PEMBELAJARAN ADVANCE ORGANIZER - Nugraha, Anton (COLLASE (Creative of Learning Students Elementary Education), 2021)
AbstractUnderstanding of the social studies subject matter of various jobs in fourth grade elementary school students is very important, because it aims to see how students think when attending the lesson. The Advance Organizer learning model is able to assist students in understanding and implementing it in the practice process directly by doing a job that is to become a figure of a farmer who is planting aloe vera plants in pots. The method used in this study uses a qualitative descriptive approach. Scenarios and implementation show the findings in the field that students can learn more actively, and creatively by the teacher providing the latest information before entering into the subject matter of learning, through the media provided by the teacher. Teacher and student responses are very good. Difficulties experienced by students in completing pre-test questions, namely the lack of social studies kurtilas textbooks provided by the school, so there are some students who fight over the textbooks when learning begins, thus disturbing the concentration of other students who are learning. Based on this research, there is an influence of the ability to think in class IV students in understanding social studies learning materials of various jobs.Keywords: Understanding types – Job types, Advance Model Organizer.